Rethinking Talent Management Strategies for Generation Z Employees in the Era of Digital Work Culture - Ria Estiana; Mohamad Kusnaeni; Aryana Satrya (Dinasti International Journal of Education Management and Social Science, 2026)
The rapid development of digital work culture has transformed organizational approaches to managing human resources, particularly among Generation Z employees who possess distinct expectations regarding flexibility, technological integration, career development, and workplace engagement. This study aims to examine the influence of talent management strategies on employee engagement and employee retention among Generation Z employees in digital work environments. A quantitative explanatory approach was employed using a survey of 180 Generation Z employees working in digital-based organizations in the Greater Jakarta area. Respondents were selected through purposive sampling, and data were collected using structured questionnaires. The data were analyzed using Structural Equation Modeling. The findings indicate that talent management strategies significantly and positively affect employee engagement and employee retention. Employee engagement also serves as a partial mediating variable in the relationship between talent management strategies and employee retention. These results suggest that organizations need to redesign conventional talent management practices by adopting more flexible, technology-oriented, and employee-centered approaches that align with the characteristics of Generation Z. This study contributes to the development of human resource management literature and provides practical insights for organizations seeking to attract, engage, and retain Generation Z talent in the era of digital work culture.